PENGARUH PEMBERIAN EFEK JINTEN HITAM (NIGELLA SATIVA) TERHADAP APOPTOSIS TERHADAP SEL EPITEKL BRONKIOLUS DAN APOPTOSIS LIMFOSIT T SALURAN NAFAS BRONCHIOLUS PADA MODEL MENCIT ASTHMA - Endang Sriwahyuni; IMAMA KHALIS NUR ARIFAH (Universitas Muhammadiyah Malang, 2010)
Abstract Airway remodelling refers to the structural changes that occur in the airway wall in asthma. These is irreversible changes to the airway, with damage of bronchiolus epithelium because the airway epithelium undergoes apoptosis as one of its manifestations. Empirically black seed has been known as bronchial asthma therapy for many years ago. The purpose of the research is to test the effect of black seed (Nigella sativa L.) extract to apoptosis of bronchiolus epithelium and apoptosis of T lymphocytes the airway bronchial asthma on asthma mouse model. Female mice were used in the expeimental laboratory research and allergic mouse model was got by given ovalbumin twice within 3 weeks intraperitoneally and 3 times per week within 6 weeks by inhalation. Black seed extract is given in 3 different dose (0,024 cc/day, 0,048 cc/day and 0,096 cc/day) for 9 weeks. Sample was chosen randomly to share it within 5 group containing 6 mice in every group ; negative control group (without any treatment, n=6), positive control group (sensitizied with ovalbumin, n=6), JH1 group (sensitizied with ovalbumin and treating with first dose of black seed extract, n=6), JH2 group (sensitizied with ovalbumin and treating with second dose of black seed extract, n=6), JH3 group (sensitizied with ovalbumin and treating with third dose of black seed extract, n=6). The parametric that is used in this research is the change in the color of the nucleus of bronchiolus epithelium and T lymphocytes the airway bronchial asthma shown the occurrence of browning apoptosis. The result shown a significant increase of apoptosis of bronchiolus epithelium on positive control group to compare with negative control group. The apoptosis of bronchiolus epithelium on JH1 shown an increase compare with positive control group. For JH2 and JH3 groups shown a decrease the apoptosis of bronchial epithelium compare with positive control group. And the research indicate that the unsignificant aptosis decrease were happen on a group with positive control instead of the group with negative control. Meanwhile, on JH1 group, apoptosis decrease were happening more significantly than the positive control group does, the aptosis increases were happen on JH2 and JH3 group, but its not capable to exceeding the positive control group apoptosis amount The conclusions is the black seed (Nigella sativa L.) extract can decrease apoptosis of bronchiolus epthelium on asthma mouse model in the third dose as the best result and the doses of black seed extract that were giving to the experiment mice can not increasing the apoptosis T Lymphocyte, thus requiring further research to figure out the perfect doses to increasing against respiratory tract apoptosis T Lymphocyte. Keyword: asthma, black seed, the apoptosis of bronchiolus epithelium, apoptosis limfosit T.